The Livelihood Challenge of Forest Honey Bee Farmers amidst COVID-19 Pandemic in Mutis, Indonesia - Njurumana, Gerson Ndawa; Riwu Kaho, Norman P.L.B.; Iswandono, Elisa; Wila Huky, Sherley S.; Mooy, Budy Z.; Fatmawati, Fatmawati; Kian, Darius A.; Nomeni, Yeni F. (Forestry Faculty, Universitas Hasanuddin, 2021)
The COVID-19 pandemic has affected various sectors of the global communities, including those that depend on forests for honey products. Furthermore, the dynamics of production and availability are completely affected by government restrictions. This study focuses on the short-term effects of the COVID-19 pandemic on the forestry sector. Specifically, it examines the pandemic effect on forest honey farmers in habitat management, harvesting, marketing, farmer institutions, and livelihoods. The study was conducted on forest honey bee farmers through field observations and structured and in-depth interviews. Data were collected using five variables and 30 indicators in Fatumnasi Subdistrict, South Central Timor Regency and analyzed using descriptive and quantitative analysis. The results showed that the COVID-19 pandemic has changed the socio-cultural and economic utilization of forest honey. Additionally, social restrictions have reduced habitat management performance, farmers institutions and livelihoods, harvesting, and marketing. This has increased pressure on the livelihoods of forest honey bee farmers than before the pandemic. Moreover, it has directly affected their lives and the ability to provide quality forest honey. Therefore, interventions are needed to strengthen marketing and institutional networks to face the changes during and after the COVID-19 pandemic.